Does China’s outward direct investment decrease carbon intensity in ASEAN countries? Evidence from CS-ARDL model analysis - Runong Xu; Gang Chen (International Journal of Climate Change Strategies and Management, 2025)
Purpose – China’s outward foreign direct investment (OFDI) in the member countries of the Association of Southeast Asian Nations (ASEAN) has increased significantly over the past few decades. However, the literature concerning FDI’s environmental effect on host countries has not reached a consensus. This paper aims to identify the effects of China’s OFDI on the carbon intensity of 10 ASEAN nations from 2003 to 2021. Design/methodology/approach – This paper applies advanced econometric techniques, such as the stationarity test, Westerlund cointegration test and cross-sectional autoregressive distributed lags (CS-ARDL) model. The novel CS-ARDL estimation technique is used to evaluate the long- and short-run effects, and this approach can address the issues of cross-sectional dependency, heterogeneity and endogeneity. Findings – The results of this investigation validate a long-term cointegrating relationship between China’s OFDI and the carbon intensity of ASEAN nations. The estimated results from the CS-ARDL model reveal that Chinese FDI is inversely related to carbon intensity. A 1% increase in Chinese FDI will decrease the carbon intensity by 0.1045% and 0.0386% in the long and short run, respectively. The empirical analyses also reveal that it takes more than a year for policies related to carbon intensity to absorb their effects and help to achieve equilibrium. In addition, the economic level and urbanization curb carbon intensity, while energy consumption and industrial structure are positively associated with carbon intensity. Originality/value – This paper is one of the first to quantitatively identify the carbon impact of Chinese direct investment in ASEAN countries. It provides the first empirical evidence for the topic using the CS-ARDL estimator, which is advantageous over other methods in analyzing both the short- and long-run effects. It is a methodological innovation in the literature on the FDI–environment nexus. Investigating how Chinese FDI affects ASEAN’s carbon intensity provides a theoretical basis for ASEAN nations to formulate more coordinated environmental and investment policies.